1996
DOI: 10.1128/jvi.70.1.617-622.1996
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination protects against in vivo-grown feline immunodeficiency virus even in the absence of detectable neutralizing antibodies

Abstract: So far, vaccination experiments against feline immunodeficiency virus have used in vitro-grown virus to challenge the vaccinated hosts. In this study, cats were vaccinated with fixed feline immunodeficiency virusinfected cells and challenged with plasma obtained from cats infected with the homologous virus diluted to contain 10 cat 50% infectious doses. As judged by virus culture, PCRs, and serological analyses performed over an 18-month period after the challenge, all of the vaccinated cats were clearly prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 52 publications
4
53
1
Order By: Relevance
“…e All the challenge strains are wild type without deletions. f Decreased FIV challenge load (5) but not against in vivo-derived challenges with heterologous FIV strains (Hesselink et al, 1999;Matteucci et al, 1996;Pu et al, 2001). Single-strain vaccines have only provided adequate protection against homologous and closely related strains but not against moderately to greatly heterologous FIV strains Elyar et al, 1997;Hesselink et al, 1999).…”
Section: Fiv Vaccine Studiesmentioning
confidence: 99%
“…e All the challenge strains are wild type without deletions. f Decreased FIV challenge load (5) but not against in vivo-derived challenges with heterologous FIV strains (Hesselink et al, 1999;Matteucci et al, 1996;Pu et al, 2001). Single-strain vaccines have only provided adequate protection against homologous and closely related strains but not against moderately to greatly heterologous FIV strains Elyar et al, 1997;Hesselink et al, 1999).…”
Section: Fiv Vaccine Studiesmentioning
confidence: 99%
“…In an SIV vaccine study, the protection observed in macaques immunized with SIV grown in human cells appears to be related more closely with an immune response directed to cell membrane antigens rather than a virus-specific immune response (Stott, 1991). However, in the FIV vaccine system, protection was reported to result from virus-specific immune responses and is not associated with immune responses against vaccine-derived cell membrane antigens Hosie et al, 1995;Matteucci et al, 1996). In this study also, antibodies against FeT-1 cell membrane antigens as well as virus-specific antibody were detected after vaccination (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…20 showing a neutralizing antibody titer < 1:10 was also protected against challenge with Petaluma virus. Studies have shown inconsistent results on the correlation between protection against FIV infection and the neutralizing antibody titer at the time of challenge Lombardi et al, 1994;Matteucci et al, 1996;Siebelink et al, 1995;Yamamoto et al, 1991b. Hosie and Flynn (1996) found that protection against challenge was correlated with the neutralizing antibody titer measured using a CrFK cell system but not with that measured in a NT assay based on the feline T cell line MBM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations